(untitled) (Dhaka University Journal of Biological Sciences, 2015)
The phytoavailability of copper (Cu) and nickel (Ni) in soils from Bangladesh was assessed. The uptake by Ipomoea aquatica and Oryza sativa L. was measured and a range of extractants tested on soils and plant tissue samples. Extractants tested were distilled water, 1 M NH4Cl, 0.01 M CaCl2, 0.005 M diethylenetriamine penta‐acetic acid (DTPA), 0.1 M ethylenediamine tetraacetic acid (EDTA), 0.1 M HCl and 1 M HCl. The extractability of the metals varied depending on the metal species, the crop and the extractant used. The best extractant was 1 M HCl, which extracted the highest amount of the heavy metals and correlated most strongly with their plant uptake measures. The use of 1 M HCl is, therefore, recommended for first‐level screening of soils contaminated with heavy metals if only one extractant is to be used. Sequential extraction showed that Cu was associated mostly with the 0.005 M DTPA and 0.1 M EDTA extractable fractions, while Ni was associated with the 0.1 M HCl and 1 M HCl fractions in most cases. The fractions of metals extracted using the sequential extraction procedure varied compared to single extractions for all soil types. Dhaka Univ. J. Biol. Sci. 24(1): 1-16, 2015 (January)